Esophagectomy in elderly patients: which is the best prognostic score?. Issue 6 (1st September 2016) - Scarpa, M.; Filip, B.; Cavallin, F.; Alfieri, R.; Saadeh, L.; Cagol, M.; Castoro, C.
Summary: Our study aimed to identify the best prognostic score for fitness for surgery and postoperative morbidity in elderly patients. A prospectively collected database of a consecutive series of patients with esophageal cancer evaluated for possible esophagectomy at our unit was analyzed. Fitness for surgery and postoperative morbidity were used as measures of outcome. The performances of the Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity (POSSUM) score, the Charlson Comorbidity Index, the age-related Charlson Comorbidity Index (ACCI), the American Society of Anesthesiologists scale and the prognostic nutritional index (PNI) were evaluated in elderly patients. Discrimination was measured with receiver operating characteristics curve analysis; calibration was assessed by the Hosmer–Lemeshow goodness-of-fit test. Age did not result a significant predictor for postoperative complications. In elderly patients, ACCI predicted the judgment of the multidisciplinary team about fitness for surgery with the best discrimination (C-index = 0.94). PNI had the best discrimination for postoperative complications (C-index = 0.71) in the elderly group. ACCI best predicted the fitness for surgery in elderly patients. In elderly patients, the most discriminative prognostic score for postoperative complication was PNI, which could be used at admission for surgery to correctly inform patients about their risk and, possibly, to take extra precaution in case of high risk.